The growth of the firm: An attention-based view - Joseph, John; Wilson, Alex J. (Strategic Management Journal, 2018)
[Research Summary: Although most theories of growth presume that growth varies with the focus and limits of managerial attention, the actual role played by attention has remained largely implicit. In contrast, this article explicitly considers attention structure and the processes that place sustained focus on growth issues. We explain how attention structure—specialized attention within a particular unit and integrated attention between units—affects both bottom-up (stimulus-driven) and top-down (schema-driven) attentional processing of new issues. We also examine the relationship between attention structure and divisional interdependencies, identifying conditions under which different attentional patterns generate organizational tensions that lead to architectural elaboration: the delineation of new organizational units. This logic is illustrated with examples from Motorola, a large telecommunications equipment provider, during a period of sustained growth. In linking theories of growth with the attention-based view (ABV), we augment both perspectives and offer an approach that provides a better understand growth's cognitive underpinnings. Managerial Summary: We examine how, within a multidivisional firm, the pattern of organizational attention affects firm growth. We highlight the attention focus within and between divisions and the corporate office and specific processes that shape the intensity and direction of attention in the firm's constituent units. In particular, we examine how corporate interventions, appointment of managerial resources, prototyping, and corporate charters direct managerial attention and the identification and advancement new opportunities in support of growth. Our approach also considers how attention patterns and formal organizational structure interact to cause tensions between managers, and when these tensions lead to the delineation of new subunits. To illustrate our logic, we use examples drawn from Motorola, a large telecommunications equipment provider, during a period of sustained growth. Our approach offers managers insights into attentional design of the multidivisional firm.]